2015
DOI: 10.35536/ljb.2015.v3.i2.a4
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Bullying and Employee Performance Among Bank Personnel in Pakistan

Abstract: This study investigates the prevalence of workplace bullying for a sample of bank employees in Lahore. It also examines whether workplace bullying (measured as work-related bullying and person-related bullying) affects employees’ performance in this context. On analyzing the data in terms of frequency and correlation, we find evidence to support the prevalence of bullying in these organizations, but none to suggest any association between workplace bullying and work performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…Hence, a hypothesis, 'ostracism has a relationship with workplace deviance' is derived. Hussain and Aslam (2015), conducted study on banking sector of Pakistan to know employees' performance and workplace bullying. Additionally, this study narrated the different concepts of work performance, bullying related to work and the person.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, a hypothesis, 'ostracism has a relationship with workplace deviance' is derived. Hussain and Aslam (2015), conducted study on banking sector of Pakistan to know employees' performance and workplace bullying. Additionally, this study narrated the different concepts of work performance, bullying related to work and the person.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have identified socio-employment challenges female bankers face in Nigeria to be sexual harassment (Pina & Gannon, 2010), work stressors predisposing to work-family conflict (Fawole & Isiaq, 2017), fear of possible workplace bullying by management or co-workers (Hussain & Aslam, 2015), job insecurity (Kunle et al, 2013), gender discrimination (Iyiola, 2011), and responsibility of pursuing unattainable financial target within a stipulated time frame (Ogechukwu, 2013). Consequently, these socio-employment challenges have the potential of engendering psychological distress like tension and frustration among female bankers, nonetheless the moderating influence of perceived-organizational justice.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Interestingly, Mukah (2020) noted that treating bankers decently and fairly enhances performance. In Nigeria, banking has been observed to be fraught with myriad of challenges for female bankers, such as sexual harassment (Pina & Gannon, 2010), work-family conflict (Fawole & Isiaq, 2017), fear of workplace bullying by management or co-workers (Hussain & Aslam, 2015), job insecurity (Kunle, Shittu, & Kolawole, 2013), and gender discrimination (Iyiola, 2011). Psychological distress can be caused by people's perceptions of unfairness and their tendencies to think, feel, and act in radicalizing way (van den Bos, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Mobbing is defined as a phenomenon characterized by hostile behaviors, actions and practices directed at one or more employees, both consciously or not, and which can damage the individual's physical or psychic integrity, besides interfering in their performance and in their work environment, and which results in losses for the individual or for the company (EINARSEN et al, 2005;BANO;MALIK, 2013;TARIQ;ALI, 2012;HUSSAIN;ASLAM, 2015;YAHAYA et al, 2012;BASHIR;HANIF, 2011;FERRAZ, 2014;COYNE, CRAIG;CHONG, 2004;CONTRERAS;LÓPEZ, 2007;LEYMANN, 1990;SILVA et al, 2017;SILVA et al 2019a;SILVA et al 2019b).…”
Section: Introductionmentioning
confidence: 99%